2021
DOI: 10.1016/j.asmr.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Pie-Crusting Technique of the Medial Collateral Ligament in the Arthroscopic Inside-out Technique for Medial Meniscal Repair With or Without Anterior Cruciate Ligament Reconstruction: A Satisfactory Repair Technique

Abstract: Purpose To assess the results of a technique for pie crusting of the medial collateral ligament (MCL) and inside-out medial meniscal repair and perform a comparison with the literature. Methods This retrospective study consisted of electronic data collection between 2012 and 2017 with a minimum of 2 years’ follow-up. The inclusion criteria were the presence of difficult medial meniscal tears with joint tightness requiring pie crusting and the presence of acute or chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the recent systematic review by Moran et al ( 20 ), a postoperative knee brace was recommended in some included studies due to the potential risk of postoperative knee instability. In detail, several authors ( 2 , 21 , 22 ) suggested a short articulating knee brace with free range of motion (ROM) for the first 2–6 weeks after surgery, while other authors ( 23 ) did not mention any brace use postoperatively. The systematic review found no adverse effects or complications in studies where patients did not receive a brace postoperatively after percutaneous MCL release ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent systematic review by Moran et al ( 20 ), a postoperative knee brace was recommended in some included studies due to the potential risk of postoperative knee instability. In detail, several authors ( 2 , 21 , 22 ) suggested a short articulating knee brace with free range of motion (ROM) for the first 2–6 weeks after surgery, while other authors ( 23 ) did not mention any brace use postoperatively. The systematic review found no adverse effects or complications in studies where patients did not receive a brace postoperatively after percutaneous MCL release ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Complications such as MCL over-release, pain and damage to surrounding structures caused by percutaneous MCL pie-crusting were addressed in several studies ( 18 - 21 ). Patients usually describe mild medial compartment pain during the first 2 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient lacked identifiable causative factors for HO, and it is unclear why he developed it in the right knee, while there was no HO in the left knee, although the same technique of sMCL pie-crusting was used. During arthroscopic PHMM tear repair, sMCL pie-crusting is commonly used to widen joint space, facilitate the repair, and avoid chondral injuries [ 14 , 15 ]. In our technique of sMCL pie-crusting, we initially mark the medial epicondyle, and an 18-gauge needle is used to puncture the skin 1.5-cm posterior and slightly distal to this point.…”
Section: Discussionmentioning
confidence: 99%